2019
DOI: 10.1097/md.0000000000017967
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic efficacy of paravertebral block for percutaneous nephrolithotomy

Abstract: Introduction: The analgesic efficacy of paravertebral block for percutaneous nephrolithotomy remains controversial. We conduct a systematic review and meta-analysis to explore the analgesic efficacy of paravertebral block for patients with percutaneous nephrolithotomy. Methods: We have searched PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases, and randomized controlled trials (RCTs) assessing analgesic efficacy of paravertebral bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
2
12
0
4
Order By: Relevance
“…No standard published guidelines exists for pain management after PCNL. Clinicians have reportedly used the inter-pleural block, renal capsular block, paravertebral block, and ICNB with varying success ( 7 , 8 , 26 , 27 ). While a recent meta-analysis has indicated that paravertebral block is effective in pain management ( 23 ), no review has synthesized evidence on the efficacy of ICNB for PCNL to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No standard published guidelines exists for pain management after PCNL. Clinicians have reportedly used the inter-pleural block, renal capsular block, paravertebral block, and ICNB with varying success ( 7 , 8 , 26 , 27 ). While a recent meta-analysis has indicated that paravertebral block is effective in pain management ( 23 ), no review has synthesized evidence on the efficacy of ICNB for PCNL to date.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians have also reported that peritubal (PT) infiltration of the nephrostomy tract with an anesthetic can reduce post-operative pain ( 6 ). Amongst nerve blocks, paravertebral, and intercostal nerve block (ICNB) are commonly used to provide post-operative pain relief after PCNL ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Case reports showed significant pain relief after ESPB for postoperative PCNL pain or renal colic. 23,24 Randomized controlled trials evaluating ESPB for PCNL found lower VAS, opioid and additional analgesic consumptions, and longer time to rescue analgesia compared to control groups. 25,26 Quadratus lumborum block (QLB) is another abdominal wall block investigated for postoperative PCNL pain control.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst PVB has become the de facto Gold Standard in chest surgery, this has yet to be acknowledged in the literature on the subject [17]. A number of studies have demonstrated the safety and efficacy of PVB to provide analgesia perioperatively in procedures affecting the kidney [18,19].…”
Section: Discussionmentioning
confidence: 99%